2016
DOI: 10.12938/bmfh.2015-011
|View full text |Cite
|
Sign up to set email alerts
|

Intake of a fermented soymilk beverage containing moderate levels of isoflavone aglycones enhances bioavailability of isoflavones in healthy premenopausal Japanese women: a double-blind, placebo-controlled, single-dose, crossover trial

Abstract: This study aimed to investigate the bioavailability of serum isoflavones after the intake of soymilk fermented by Lactobacillus casei strain Shirota containing 32.5% isoflavone aglycones (FSM) or placebo soymilk containing no isoflavone aglycones (SM). In a double-blind, placebo-controlled, single-dose, crossover trial, 7 healthy premenopausal Japanese women (mean age: 35.3 ± 11.0) consumed FSM or SM on day 1 and crossed over to the other soymilk after a 6-day washout period. Serum isoflavones in blood samples… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 27 publications
1
13
0
Order By: Relevance
“…The fermentation, which increases the aglycone content of biscuits up to 97% (supporting information, Table S1), improved isoflavone absorption and metabolism in human intestine. In general, it is reported that isoflavone aglycones are absorbed in greater amounts than glycoside forms, and thus soy foods rich in aglycones, such as FSBM biscuits, show higher absorption of isoflavones than soy foods rich in glycosides, such as SBM biscuits . Isoflavone aglycones have lower molecular weight and higher lipophilicity when compared to glycosides due to the absence of a sugar moiety in their chemical structures, which facilitates their absorption by enterocytes.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The fermentation, which increases the aglycone content of biscuits up to 97% (supporting information, Table S1), improved isoflavone absorption and metabolism in human intestine. In general, it is reported that isoflavone aglycones are absorbed in greater amounts than glycoside forms, and thus soy foods rich in aglycones, such as FSBM biscuits, show higher absorption of isoflavones than soy foods rich in glycosides, such as SBM biscuits . Isoflavone aglycones have lower molecular weight and higher lipophilicity when compared to glycosides due to the absence of a sugar moiety in their chemical structures, which facilitates their absorption by enterocytes.…”
Section: Resultsmentioning
confidence: 99%
“…Isoflavone aglycones have lower molecular weight and higher lipophilicity when compared to glycosides due to the absence of a sugar moiety in their chemical structures, which facilitates their absorption by enterocytes. Glycoside forms need to be hydrolyzed to aglycones by intestinal enzymes and/or gut microbiota in order to be absorbed, which also may explain differences between absorption of aglycones and glycosides …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The three isoflavones genistein, daidzein and glycitein and their respective glycosides account for approximately 50%, 40% and 10%, respectively, of the total isoflavone content of soybeans [68]. There is disagreement over whether isoflavone form affects total absorption; some studies show that in comparison to the glycoside, aglycone isoflavones are absorbed faster and to a greater extent [74,75,76] whereas other studies show aglycones are absorbed more quickly but total absorption is the same or even less [77,78,79]. In this document isoflavone amounts are expressed in aglycone equivalent weights.…”
Section: Isoflavonesmentioning
confidence: 99%
“…They can be classified into fermented (tofu, okara, yuba, fresh greed soybeans, whole dry soybeans, soy nuts, whole-fat soy flour, soy sprouts, soymilk and soymilk products) and nonfermented (tempeh, natto, miso, fermented tofu and soymilk products and soy sauces) products [46]. Epidemiological studies among the Japanese population suggest that fermented soybean products have better effects than nonfermented soy products, probably because of a higher bioavailability of isoflavone aglycones [47].…”
Section: Dietary Intake and Sources Of Isoflavonesmentioning
confidence: 99%